An ultra-high resolution water isotope record (d18O, dD) from the Renland ice cap spanning 120,000 years of climate history - Vasileios Gkinis; Bo Møllesøe Vinther; Eliza Cook; Johannes Freitag; Christian T Holme; Abigail G Hughes; Sepp Kipfstuhl; Helle Astrid Kjær; Niccolò Maffrezzoli; Valerie Morris; Trevor J Popp; Sune Olander Rasmussen; et al. (PANGAEA, 2024)
The RECAP ice core was drilled at the Renland ice cap (71.30°N, 26.72°W, 2315 m asl) in 2015 from the surface to bedrock at a final depth of 584 m. Due to its close proximity to the east Greenland coast the record provides us with climate information reflecting past changes at the margins of the Greenland Ice Sheet. Stable water isotope ratios in polar ice record hydrological cycle changes due to isotope fractionation processes, occurring during evaporation, transportation and condensation. Here we present ultra high resolution water isotope measurements (δ18O, δ2H) obtained with Infrared-Laser Spectroscopy coupled to a state-of-the-art continuous melting system for ice core analysis. The measurements are calibrated to the VSMOW-SCALE following a daily two-point calibration. We used well defined local water standards calibrated against the primary IAEA standard waters. Using the results from the repeated VSMOW-SLAP calibrations we deduce an accuracy level of 0.02 and 0.3 extperthousand for δ18O, δ2H respectively. Using spectral methods we estimate the compound noise level of the measurements directly from the δ18O and δ2H signals to be 0.08 and 0.2 extperthousand respectively. Gaps in the record are filled using an iterative Maximum Entropy Method interpolation algorithm by Fahlmann and Ulrych (1982). The age scale is based on a linear interpolation of the water isotope record on the RECAP GICC05modelext Time Scale (version 1/3-2018 - PANGAEA, https://doi.org/10.1594/PANGAEA.906108).